Faktor-Faktor Yang Mempengaruhi Motivasi Kerja SDM Kesehatan Di UPTD Puskesmas Kerkap Kabupaten Bengkulu Utara - Pebriani, Emi; Azisah, Danur; Munte, Fitriana; Marlianto, Nuche; Anggraini, Gita Santi (Jurnal Dehasen Untuk Negeri, 2026)
Motivation is the drive that arises within a person to do something in order to achieve organizational goals and fulfill needs. Nurse performance is influenced by a person's abilities, rewards, length of service, and relationships within the organization (Srsaid Suni, 2018). Nurse performance affects patient safety and satisfaction. This study aims to determine the factors that influence the work motivation of health human resources at the Kerkap Community Health Center UPTD. This study was conducted from June 23 to 25, 2025, using a cross-sectional design. The population in this study consisted of all human resources at the Kerkap Community Health Center UPTD in North Bengkulu Regency, totaling 56 respondents, using total sampling technique. Data were collected through questionnaires and analyzed using univariate and bivariate analysis with the chi-square test. The results showed that almost all respondents were over 30 years old, totaling 44 respondents (78.5%), almost all respondents were female (91.07%), almost half of the respondents were contract workers (42.85%), had a D3 education (87.8%), and had worked for more than 5 years (56.1%). In addition, 41.07% of respondents had low motivation, 60.71% received low rewards, and 53.57% showed poor performance.Recommendation:To improve supervision of human resources through monitoring and evaluation of all health service activities.